Pengaruh Literasi Keuangan Syariah, Pendapatan dan Gaya Hidup terhadap Minat Menabung di Bank Syariah pada Masyarakat Kecamatan Cibinong Kabupaten Bogor - Junaedi, Dedi; Salistia, Faisal; Raihan , Muhammad (ManBiz: Journal of Management and Business, 2026)
Financial planning is a factor that can lead a society into financial problems if not implemented properly, as it is the process of managing an individual’s finances to achieve personal economic satisfaction. This study aims to determine the influence of Islamic financial literacy, income, and lifestyle on the interest in saving at Islamic banks among the community in Cibinong District, Bogor Regency. The research uses a quantitative method with 100 respondents selected through purposive sampling. Data were analyzed using multiple linear regression via SPSS. The results show that Islamic financial literacy and income have no significant effect on saving interest, while lifestyle has a positive and significant effect. Simultaneously, the three independent variables significantly influence saving interest, with an F-value of 92.033 > 2.70 and a significance level of 0.00 < 0.05. Keywords: Islamic Financial Literacy; Income; Lifestyle; Saving Interest; Sharia Bank;